QUALITY OF LIFE AND MENTAL EMOTIONAL HEALTH OF ELDERLY PEOPLE - Alfrina Hany (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2018)
The higher dependence rate of elderly people in Ponorogo can make their quality of life lower.Unfortunately, how the quality of life can influence the mental emotional health is still unknown. The purpose of this research was to identify the influence of the quality of life to mental emotional disorders of older adults. The design of this research was Observational correlational with cross sectional approach. This research was held at 4 working areas of health facilities in Ponorogo district in East Java from March to May in 2015.This study included 200 elder people as participants and 50 sampling quota in each health facilities. The data collection in this study was assessed with 2 instruments. First instrument was used in this study developed by World Health Organization in Quality of life (WHO QOL-BREF) and second instrument was Self Reporting Questionnaire (SRQ). The Pearson Correlation test was performed in this study (SPSS version 20) . The researchers found out that there was an influence of quality of life (physical health, psychologic, social relationship, and environment) on mental emotional disorders in elder people (p-Value < 0.05). This result revealed that quality of life in older adults influenced the mental emotional disorders. The improvement actions that can be proposed to decrease the mental emotional disorders of the elderly are the elderly are able to have an easy and quick access to health and general service facilities to support the mental well being of older people.